Distribution, mobility and exposure risk of rare earth elements, uranium and thorium in soils impacted by illegal cassiterite–monazite mining in the southeastern Amazon, Brazil - Antonia Andreyna Pereira Rodrigues; José Tasso Felix Guimarães; Gabriel Caixeta Martins; Luiza Santos Reis; Edna Santos de Souza; Roberto Dall’Agnol; Sílvio Junior Ramos (Environmental Geochemistry and Health, 2026)
Abstract Illegal cassiterite and monazite mining in the Taboca district of São Félix do Xingu, southeastern Amazonia, Brazil, reworks alluvial materials developed on the Paleoproterozoic Antônio Vicente Granite. This A-type granite is naturally rich in the REE-, Th- and U-bearing minerals monazite, xenotime and zircon, so mining further concentrates rare earth elements (REE), thorium and uranium whose concentrations are already raised by lithology. We sampled 130 surface horizons (34 native soils, 96 tailing residues) and analyzed them by chondrite-normalized REE patterns, mass-transfer coefficients against a niobium-tantalum composite, ethylenediaminetetraacetic-acid (EDTA) extraction, redundancy analysis and locally derived contamination index. Native soils carry two mineralogical signatures: light REE with thorium tracking detrital monazite, and heavy REE with yttrium tracking xenotime and zircon. Europium anomalies are strongly negative throughout. Tailings concentrate heavy-mineral phases while losing most of the soil reactivity. Organic matter drops from 2.15 to 0.54%, effective cation exchange capacity from 3.23 to 1.29 cmolc dm −3 , and aluminum saturation rises from 2.85 to 16.35%. EDTA-extractable fractions of the heavy REE and yttrium climb above 24% (ytterbium 24.6%; lutetium 24.3%). The geoaccumulation index places residues in moderate-to-extreme classes for middle and heavy REE plus yttrium. The cumulative hazard index for non-radiological exposure crosses 1 for adult miners (1.0–3.7) and reaches 18–67 for child residents. Predicted-environmental versus no-effect concentration ratios in surface water exceed 1 for lanthanum, cerium, neodymium, thorium, yttrium, ytterbium and uranium, identifying these as monitoring priorities. A source-rock-aware baseline is essential to separate mining-derived contamination from naturally elevated geogenic backgrounds in tropical tin–rare-earth provinces.